2020
DOI: 10.1177/1354856520913865
|View full text |Cite
|
Sign up to set email alerts
|

‘Weekends became something other people did’: Understanding and intervening in the habitus of video game crunch

Abstract: ‘Crunch’ – a period of unpaid overtime meant to speed up lagging projects – is a common labor practice in the video game industry and persists despite many costs to developers. To understand why, we conducted a critical discourse analysis of Game Developer magazine (2000–2010) to explore how industry members perceive and discuss gamework (1) in a publication for developers, by developers and (2) during the first decade in which serious conversations about labor emerge in the games industry. Our analysis found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
0
13
0
4
Order By: Relevance
“…Crunch culture refers to a much-criticized labor practice of working unpaid for overtime, to speed up projects (see e.g. Peticca-Harris et al, 2015;Cote & Harris, 2020), and while the problem has been identified, it seems to persist (Legault & Weststar, 2017). Crunch culture is especially discriminating against women (Consalvo, 2008) or others with caring responsibilities (Legault & Weststar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Crunch culture refers to a much-criticized labor practice of working unpaid for overtime, to speed up projects (see e.g. Peticca-Harris et al, 2015;Cote & Harris, 2020), and while the problem has been identified, it seems to persist (Legault & Weststar, 2017). Crunch culture is especially discriminating against women (Consalvo, 2008) or others with caring responsibilities (Legault & Weststar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Working in esports provides an avenue for gamers to continue their leisure gaming practices and might be thought of as a form of "serious leisure", becoming an "improvement over work" that allows for selffulfillment (Stebbins 1982). Working in the game development provides similar opportunities, since the promise of enjoyable work draws individuals who have played games for a long time and enjoy the prospect of developing games as a career (Cote and Harris 2020). The "work as play" ethos within the game development industry is especially attractive as it seems to offer workers flexibility, autonomy, and of course, the opportunity to play games as part of their work (de Peuter and Dyer-Witheford 2005).…”
Section: The Games Industry In Singaporementioning
confidence: 99%
“…The game industry has achieved some notoriety in the press, given the work conditions that employees are subject to. Game developers experience crunch time (Consalvo 2008), which refers to a "period of extended working hours to speed up lagging projects"; it is frequently extensive and unpaid though it is a practice that is endemic to the game development industry (Cote and Harris 2020). On the one hand, passion supported game designers in making meaningful products.…”
Section: Developer-employer Role Relations: Passionate Labor As Profitable Exploited Workmentioning
confidence: 99%
See 2 more Smart Citations